Liquidity Effects on the Simultaneity of Trading Volume and Order Imbalance - Arfianto, Erman Denny; Kusumastuti, Nurita (Universitas Negeri Semarang, 2016)
The purpose of this research is to analyze the simultaneity between trading volume and order imbalance, the influence of past performance, market risk, market capitalization, tick size to the trading volume and the influence of tick size, depth and bid-ask spread to the order imbalance of companies that were listed on LQ 45 index. The samples in this research were selected by using the purposive sampling method with some selected criteria. Fifty-five companies listed on 2014’s LQ 45 index were chosen as the sample. The results showed that the trading volume is simultaneously related to the order imbalance; past performance, market risk, and market capitalization have the positive and significant effect to the trading volume; tick size has the negative and significant effect to the trading volume; the order imbalance has the negative and insignificant effect to the trading volume; tick size, depth, bid-ask spread, and trading volume have no significant effect to the order imbalance.